2012
DOI: 10.1002/dvdy.23737
|View full text |Cite
|
Sign up to set email alerts
|

Astacin‐like metallo‐endopeptidase is dynamically expressed in embryonic stem cells and embryonic epithelium during morphogenesis

Abstract: Background: Astacin-like metallo-proteases are zinc endopeptidases conserved among vertebrates and invertebrates. First described as hatching gland enzymes, many members of the family possess other functions during embryonic development. In the chick, however, functions of Astacin-like proteins remain elusive. Results: We report here that Astacin-like (ASTL) is strongly expressed in mouse and chicken embryonic stem (ES) cells and exhibits a very dynamic expression pattern during embryogenesis and organogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Evolutionary analysis of astacin-like metalloproteases in the medaka and zebrafish genomes [16] demonstrated that one or two genes represent bona fide “hatching enzymes”, while the rest are paralogous copies of still unclear function. A recent study [71] revealed that these proteins are involved in mouse and chicken embryogenesis and organogenesis, mostly in remodelling epithelia. Whether astacin-like metallo-endopeptidases have a similar role in the common sole and, more specifically, in promoting cellular/tissue migration through ECM reorganisation during early development represents an interesting topic for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary analysis of astacin-like metalloproteases in the medaka and zebrafish genomes [16] demonstrated that one or two genes represent bona fide “hatching enzymes”, while the rest are paralogous copies of still unclear function. A recent study [71] revealed that these proteins are involved in mouse and chicken embryogenesis and organogenesis, mostly in remodelling epithelia. Whether astacin-like metallo-endopeptidases have a similar role in the common sole and, more specifically, in promoting cellular/tissue migration through ECM reorganisation during early development represents an interesting topic for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…To date, SAS1B has been proposed to function in blastocyst hatching [ 43 ], sperm-egg interaction [ 1 ], the block to polyspermy [ 3 ], epithelial cell behaviour during early development in chick [ 44 ], and as a secretory protein released by oocyte activation [ 45 ]. Previously proposed translational applications of ASTL include its use as an ovarian cyst fluid biomarker [ 46 ] and target for an oocyte-specific contraceptive [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, until now REX1 (ZPF42) and UTF1 have not been found in the avian genome. Therefore, genes expressed in undifferentiated, long-term proliferating cESCs include SOX3, POUV (POU5F3), DNMT3B, EPCAM, CLDN1, VGLL2, EOMES, CFC1B, GATA5, NANOG, ESRP2, OTX2, TRIM71, GATA4, FOXA2, LIN28A, ASTL, ENS-1, CDH1 and SALL4 (Jean et al, 2015;Vautherot et al, 2017;Acloque et al, 2012;unpublished data). These genes encode transcription factors, DNA demethylases, and cell adhesion molecules.…”
Section: Molecular Profilementioning
confidence: 99%